(untitled) (The Pakistan Development Review, 2017)
In this study, an attempt has been made to estimate the incidences of the job mismatch and its determinants in Pakistan. This study has divided the job mismatch into three categories: qualification-job mismatch, skill mismatch and field of study mismatch. The primary dataset has been used in which employed graduates of the formal sector have been targeted. The paper has also measured the qualification-job mismatch by three approaches, and found that about one-third of the graduates have been facing qualification-job mismatch. Similarly, more than one-fourth of the graduates are mismatched in skills, about half of them are over-skilled and the rest are under-skilled. The analysis also shows that 11.3 percent of the graduates have irrelevant, and 13.8 percent have slightly relevant jobs to their field of study. The analysis reveals that over-qualified and over-skilled graduates are less satisfied, while under-qualified and under-skilled graduates are more satisfied with their current jobs. A similar situation has been observed in case of the field of study mismatch, where both the moderate and complete fields of study matched graduates are more satisfied than the mismatched ones. The job search behaviour is positively associated with the level of education. Over-qualification has a positive impact, while under-qualification has a negative effect to search for another job. A good match between field of study and current job reduces the likelihood of intention to quit the job. JEL Classification: I23, I24, J21, J24 Keywords: Education and Inequality, Higher Education, Human Capital, Labour Market